Risk-based Peer-to-peer Energy Trading with Info-Gap Approach in the Presence of Electric Vehicles - Seyyedeh-Barhagh, Sahar; Abapour, Mehdi; Mohammadi-Ivatloo, Behnam; Shafie-khah, Miadreza (Elsevier, 2023)
Small-scale smart microgrid is prone to economic consideration of adequate transactive energy sharing and reliable certified power pool hub. Moreover, direct integration of efficient with renewable energy providers in presence of storage such as electric vehicle (EV) aggregation improves the performance of energy systems and guarantees secure trade among the consumers. However, unified modeling of the energy community framework faces the challenge of load management. In this paper, an optimal risk management procedure is proposed for renewable-based prosumers such as photovoltaic (PV), and EV to maximize the horizon of uncertainty parameter. The energy demand in peer-to-peer (P2P) household energy sharing is considered as the uncertain parameter. To this end, in order to study the behavior of a risk-averse and a risk-seeker decision-maker, an information-gap decision theory (IGDT) probability model is applied. In order to demonstrate the performance of the proposed approach, the model is implemented in a test microgrid and the simulation results are presented and discussed.
Keywords: Peer to peer (P2P) trading; Risk management; Electric vehicle (EV); Information gap decision theory (IGDT); fi=Sähkötekniikka|en=Electrical Engineering|